Anti-Diabetic Activities of Hydro-Methanolic Crude Extract and Solvent Fractions of Heteromorpha arborescens (Apiaceae) Leaves in Mice - Zeleke YG; Atnafie SA; Aragaw TJ (Dove Medical Press, 2023)
Yeshiwas Guadie Zeleke,1 Seyfe Asrade Atnafie,2 Tezera Jemere Aragaw2 1College of Medicine and Health Sciences Comprehensive Specialized Hospital, University of Gondar, Gondar, Ethiopia; 2Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tezera Jemere Aragaw, Tel +251918773670, Fax +2510581141240, Email tezeraadis1982@gmail.comBackground: Heteromorpha arborescens has been used to treat diabetes traditionally. There was no in vivo study to support the claim. This study aimed to confirm anti-diabetic activity of 80% methanol in water extract and solvent fractions of H. arborescens leaves in mice.Methods: H. arborescens leaves were macerated and extracted in 80% methanol in water. Hydro-methanol extract of H. arborescens leaves were tested in mice models. Overnight fasted mice were randomly divided into five groups for normoglycemic and glucose-loaded models as a negative control, positive control, and three tested groups, whereas, in streptozotocin-induced diabetic models, the mice were grouped into six groups each comprised six mice: diabetic negative control and normal negative control groups treated with 10 mL/kg distilled water, diabetic positive control group treated with Glibenclamide 5 mg/kg and three diabetic tested groups treated with extract at 100, 200, and 400 mg/kg doses. A one-way ANOVA was performed to analyze the data, and the post hoc Tukey's test was utilized for multiple comparisons. The P-value < 0.05 was considered statistically significant.Results: Hydro-methanol extract of H. arborescens leaves at 400 mg/kg in normoglycemic mice significantly lowered blood glucose levels (BGLs) (P< 0.01). Mice with oral glucose-loaded test lowered BGLs at dosages of 200 mg/kg (P < 0.05) and 400 mg/kg (P < 0.01) respectively. Single-dose of ethyl acetate, n-hexane fractions and hydro-methanol extract at 100 mg/kg, 400 mg/kg and 200 mg/kg reduced BGLs (P < 0.05, P < 0.001, and P < 0.01) respectively. BGL drops in diabetic mice given daily repeated doses of 200 mg/kg of hydro-methanol extract and 400 mg/kg of ethyl acetate fraction (P < 0.001). Diabetic mice gained weight at a 400 mg/kg hydro-methanol extract and ethyl acetate fraction (P < 0.05 and P < 0.01) respectively. Hydro-methanol extract and ethyl acetate fraction and at 200 mg/kg decreased total cholesterol, triglycerides, and low-density lipoprotein and increased high-density lipoprotein (P < 0.001).Conclusion: 80% methanol in water extract and solvent fractions of H. arborescens leaves showed anti-diabetic effects and significantly reduced hyperlipidemia in diabetics, this study supported the traditional usage of H. arborescens for treating diabetes; however, species variation could also limit such a straightforward extrapolation of the findings of this study in humans.Keywords: antidiabetic, Heteromorpha arborescens, in vivo